1999
DOI: 10.1128/mcb.19.3.2212
|View full text |Cite
|
Sign up to set email alerts
|

A Human Sequence Homologue of Staufen Is an RNA-Binding Protein That Is Associated with Polysomes and Localizes to the Rough Endoplasmic Reticulum

Abstract: In the course of a two-hybrid screen with the NS1 protein of influenza virus, a human clone capable of coding for a protein with high homology to the Staufen protein from Drosophila melanogaster (dmStaufen) was identified. With these sequences used as a probe, cDNAs were isolated from a cDNA library. The encoded protein (hStaufen-like) contained four double-stranded RNA (dsRNA)-binding domains with 55% similarity and 38% identity to those of dmStaufen, including identity at all residues involved in RNA binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
184
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(202 citation statements)
references
References 52 publications
(50 reference statements)
17
184
0
1
Order By: Relevance
“…Bioinformatics analysis of the footprints, however, failed to identify any particular enriched motif (A.K. and E.P.R., unpublished data), results consistent with the idea that Staufen recognizes dsRNA in a sequence-independent manner [39][40][41] .…”
Section: Discussionsupporting
confidence: 60%
“…Bioinformatics analysis of the footprints, however, failed to identify any particular enriched motif (A.K. and E.P.R., unpublished data), results consistent with the idea that Staufen recognizes dsRNA in a sequence-independent manner [39][40][41] .…”
Section: Discussionsupporting
confidence: 60%
“…Finally, the isolation of Staufencontaining particles by Mallardo et al (19) has confirmed the previous suggestion that there are two pools of both Staufen 1 and 2 in mammalian neurons (24,25). One pool fractionates with endoplasmic reticulum (ER) in their biochemical experiments and may represent Staufen observed in large granules that colocalize with the rough ER within the soma or at synaptic terminals (22,26,28,32,33 …”
supporting
confidence: 63%
“…Recently, two homologues of Staufen have been identified in mammals: Staufen 1 (22)(23)(24)(25)(26) and Staufen 2 (27)(28)(29). Both Staufen 1 and 2 are expressed in the nervous system; both proteins contain several dsRBDs and have a tubulin-binding domain (22)(23)(24)(25)(26)(27)(28)(29). What role could Staufen be playing in the mammalian nervous system?…”
mentioning
confidence: 99%
“…To study these RNA-containing particles in detail, we set out to biochemically isolate these complexes on the basis of two criteria. First, we chose Stau1 (13,23,24) and Stau2 (16,17) proteins, as biochemical markers to follow their isolation. Second, we assumed based on an attractive model (10) that the observed Staufen-containing moving particles represent soluble RNPs not associated with membranes.…”
Section: Resultsmentioning
confidence: 99%